Individualism, synchronized stock price movements, and stock market volatility. Issue 3 (29th May 2019) - Zhan, Feng
Abstract : Purpose: The purpose of this paper is to examine the impact of national culture on herding behavior across international financial markets. Design/methodology/approach: The relation between national culture and investor behavior, and how it impacts overall market volatility is studied by examining synchronized stock price movements and stock market volatility in 47 countries around the world over the period of January 2003–May 2012. Findings: The author finds that nations with lower values of individualistic culture are more likely to have a higher number of synchronized stock price movements. Further, the correlation between stock price movements apparently increases stock market volatility. Nations with high individualistic culture have a lower number of synchronized stock price movements and, thus, have lower levels of stock market volatility. The positive relationship between synchronized stock price movements and stock market volatility is stronger for emerging markets during the financial crisis from June 2007 to December 2008. Originality/value: The empirical results in this paper indicate that a portion of the difference in market level volatility is attributed to the investor bias of different cultures. Investor behavior bias creates excess volatility that drives stock prices away from fundamentals. This impact is strong in nations with lower individualistic culture. The result from this research could also have a wide implication in the investment industry.